Empirical Study of Bandung Basin Tourist Behavior: Visitor Journey Analysis - Marceilla Suryana; Eko Susanto; Syifaa Novianti; Chandra Budhi Septyandi (Business Education Program of Universitas Pendidikan Indonesia, 2023)
This study aims to provide a comprehensive understanding of tourist travel in the Bandung Basin and formulate strategic recommendations to improve the tourist experience in the area. Using quantitative research methods involving 300 tourist respondents visiting destinations in the Bandung Basin, this study examines travel in various stages, including pre-visit, in-visit, and post-visit. It highlights the implications for DMO and stakeholders in the tourism industry. This study found that this region's dreaming and planning phases are largely determined by the trend and influence of digital information received by travelers. While at the booking stage, the role of online travel agents in the younger generation of travelers dominates its utility above direct bookings. This study provides several strategic recommendations for DMO to follow up on the profile of tourist behavior in the Bandung Basin.